Ameliorating the anticancer drug ”Adriamycin” acute Cardiotoxicity by Rosuvastatin and Telmisartan in rats - Ahmed, Ihab A. (Iraqi Journal of Cancer and Medical Genetics, 2014)
Adriamycin, an anthracycline antibiotic is a powerful antineoplastic drug, but its therapeutic usefulness is limited by its cardiotoxicity. The present study investigated the effects of pretreatment with rosuvastatin and telmisartan alone or in combination against adriamycin induced cardiotoxicity in rats using biochemical approaches. The animals were divided into eight groups of 5 animals each. The first group received no drug(s) po but a single dose of distilled water (7.5 ml/kg, ip) at day eight, which serves as the control group. The second group received no drug(s) po but a single dose of adriamycin (15 mg/kg, ip) at day eight, and serves as adriamycin only received group. The third and sixth group received rosuvastatin (2 , 10) mg/kg/day respectively for nine days, and on day eight, one hour after drug administration, a single dose of adriamycin (15 mg/kg, ip) was given. The fourth and seventh group received telmisartan (2 , 4) mg/kg/day respectively for nine days, and at day eight, one hour after drug administration, a single dose of adriamycin (15 mg/kg, ip) was given. The fifth and eighth group received both drugs, where the fifth group Received both of rosuvastatin (2 mg/kg, po) and telmisartan (2 mg/kg, po), 1 hour apart, daily for nine days, and on day eight, one hour after drug administration, a single dose of adriamycin (15 mg/kg, ip) was given. While the eighth group received both of rosuvastatin (10 mg/kg, po) and telmisartan (4 mg/kg, po), 1 hour apart, daily for nine days, and on day eight, one hour after drug administration, a single dose of adriamycin (15 mg/kg, ip) was given. At day ten of the study, blood samples were taken for biochemical analysis. Rats treated with adriamycin showed cardiotoxicity as evidenced by elevation of serum lactate dehydrogenase (LDH) activity, serum malondialdehyde (MDA) level, cardiac troponin (CTn-I) level and interluekine 17(IL-17) level. Pretreatment with rosuvastatin and telmisartan alone or in combination elicited a significant decrease in the activities of all markers measured in comparison with adriamycin treated group. These results suggest that both rosuvastatin and telmisartan treatment provides a significant protective effect against acuteadriamycin induced cardiotoxicity in rats.